To Determine The Risk Factors and Indications of Emergency Peripartum Hysterectomy - Amina Hafeez, Shumaila Yasin, Saba Fatima, Sabeena Umer, Shazia Roman, Faiza Irshad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of factors leading to emergency peripartum hysterectomy Introduction: The emergency peripartum hysterectomy (EPH) is a dreadful complication and to determine its risk factors is very important to early and prompt management. Objective: My objective is to determine the frequency of factors leading to emergency peripartum hysterectomy. Main outcome: EPH is the main outcome which is surgical removal of uterus due to severe postpartum hemorrhage Study design: Descriptive case series Setting: Obstetrics and Gynaecology Department, District Headquarter Hospital, Gujranwala Duration of study: 1 July 2019 to 31 December 2019 Material and methods: Seventy patients undergoing emergency peripartum hysterectomy were selected from the Obstetrics and Gynecology emergency department of District Headquarter Hospital, Gujranwala. Hospital registration numbers was noted and for all enrolled women. The major risk factors like uterine atony, uterine rupture and abnormal placentation was noted down from detailed history and clinical and ultrasound examinations and surgeon notes was collected. All patients will be efficiently managed throughout a per standard guidelines. Data was analyzed using SPSS version 20. The quantitative variables were age, gestational age and BMI. Mean and standard deviation was calculated for quantitative data. Frequency and percentages were calculated for qualitative data like parity and risk factors. Effect modifiers like age, parity and BMI was controlled by stratification. Post stratification Chi square test was applied. P value ≤ 0.05 was considered as statistically significant. Results: The mean age was 28.64 ± 6.836 years. The mean gestational age and BMI were 31.61 ± 3.576 weeks and 23.66 ± 2.904 kg/m2 respectively. The frequency of parity groups was as follows; for parity 1, 2, 3, 4 and ≥5 was 13 (18.6%), 10 (14.3%), 11 (15.7%), 25 (35.7%) and 11 (15.7%) respectively. The main causes of EPH were uterine rupture, abnormal placentation and uterine atony with proportions of 30%, 44.3% and 12.9% respectively. The data was stratified according to age, gestational age, parity and BMI. The results showed that there was no significant impact of age, gestational age, parity and BMI as all p values were >0.05 Conclusion: The emergency peripartum hysterectomy has various causative factors and uterine rupture, abnormal placentation and uterine atony are the most significant factors which can be minimized to reduce its incidence.